LATE NEOPROTEROZOIC PROTO-ARC OCEAN CRUST IN THE DARIV RANGE, WESTERN MONGOLIA: A SUPRA-SUBDUCTION ZONE END-MEMBER OPHIOLITE - Dijkstra A.H.; Buchan C.; Brouwer F.M.; Cunningham W.D.; Badarch G.; Mason P.R.D. (My University, 2006)
An unusual late Neoproterozoic (c. 572 Ma) ophiolite is exposed in the Dariv Range (western Mongolia, which contains intermediate to acidic lavas and sheeted dykes, and an igneous layered complex consisting of gabbro-norites, websterites, orthopyroxenites and dunites underlain by serpentinized mantle harzburgites. Based on the compositions of the crustal units and the crystallization sequences in the mafic and ultramafic cumulates we conclude that the entire oceanic crust, including the cumulates, was made from are magmas with boninitic characteristics. The Dariv rocks bears a strong resemblance to rocks recovered from the modern Izu-Bonin-Mariana Fore-arc, a fragment of proto-arc oceanic basement, and we propose that the Dariv Ophiolite originated in a similar tectonic setting. A metamorphic complex consisting of amphibolite- to granulite-facies metasedimentary and meta-igneous rocks was thrust over the ophiolite. This metamorphic complex probably represents a Cambrian arc. Thrusting started before 514.7 ± 7.6 Ma as constrained by new sensitive high-resolution ion microprobe U-Pb zircon analyses from a syn-to post-tectonic diorite. The Dariv Ophiolite ia a type-example of a proto-are ophiolite, a special class of supra-subduction zone ophiolites.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская